Is research a global public good? - Pinstrup-Andersen, Per (2001)
Research, and in particular biological research, today is very likely to be patented and thus may not benefit the poor in the developing countries. It is no longer a public good. This heavily contradicts with the initial objective of biological or agricultural research to contribute to food security and poverty alleviation. This situation calls for new initiatives to fund public research in general and national and international agricultural research systems in particular.